Particle dynamics in the injector of ion linear induction accelerator - Karas’, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2019)
The investigations of the particle dynamics in the injector of a linear induction accelerator (LIA) in the presence of an accelerating electric field and a uniform longitudinal magnetic field of various magnitudes have been presented. It is shown that at found parameters of the system and particles the ion beam at the exit of the injector keeps the transverse dimensions and its current close to the initial, that allows to count on the accomplishment of its further transportation through the LIA section. Проведено дослідження динаміки частинок в інжекторі лінійного індукційного прискорювача (ЛІП) при наявності прискорюючого електричного і однорідного поздовжнього магнітного полів різних величин. Показано, що при знайдених параметрах системи і частинок іонний пучок на виході з інжектора зберігає поперечні розміри та струм, близькими до первинних, що дозволяє розраховувати на реалізацію його подальшого транспортування через секцію ЛІП. Проведены исследования динамики частиц в инжекторе линейного индукционного ускорителя (ЛИУ) при наличии ускоряющего электрического и однородного продольного магнитного полей различных величин. Показано, что при найденных параметрах системы и частиц ионный пучок на выходе из инжектора сохраняет поперечные размеры и ток, близкими к первоначальным, что позволяет рассчитывать на реализацию его дальнейшей транспортировки через секцию ЛИУ.